PENGEMBANGAN SOAL MATEMATIKA KONTEKSTUAL BERBASIS HOTS DENGAN KEARIFAN LOKAL JAMBI PADA MATERI PERKALIAN KELAS III SD - Helena; Eka Sastrawati; Andi Gusmaulia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to describe the development process, validity, and reliability of contextual mathematics problems based on High Order Thinking Skills (HOTS) by integrating Jambi's local wisdom into multiplication material for 3rd-grade elementary school students. This study uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The research instruments include validation sheets for material and language experts, as well as test instruments for reliability testing. The results show that the development process through five systematic stages produced 5 HOTS-based questions integrating Jambi's culture such as Candi Muaro Jambi and Batik Jambi motifs. The validity results from material and language experts reached the "Very Valid" category, indicating the content and linguistic aspects are highly appropriate. The reliability test results yielded a coefficient of 0.51, categorized as moderate reliability. This research concludes that the developed product is feasible for use as an evaluation tool in elementary schools.